STUDENTS DIFFICULTIES IN PASSING LISTENING SECTION IN TOEFL PREDICTION TEST - Chairuddin Chairuddin; Maria Ulfa (Program Studi Pendidikan Sejarah - Universitas Samudra, 2018)
The title of the research “students difficulties in passing listening section in Toefl prediction Test”, this research use qualitative method. The research need to obtain:what the students difficulties in passing listening section in toefl prediction test.There are twenty students as the respondents of the research. The instrument that used in this research is questioner. The result of the research found that there are several aspects of students difficulties, and the mostdifficulties things are : 1) Catch the speaker idea ,2) identify idiomatic expression,3) Identify the cohesive marker, 4) Assign a literal meaning to the utterance,5) Retain the important information.